Fabrication of High-Density Out-of-Plane Microneedle Arrays with Various Heights and Diverse Cross-Sectional Shapes - Roh, Hyeonhee; Yoon, Young Jun; Park, Jin Soo; Kang, Dong‑Hyun; Kwak, Seung Min; Lee, Byung Chul; Im, Maesoon (Nano-Micro Letters, 2021)
Out-of-plane microneedle structures are widely used in various applications such as transcutaneous drug delivery and neural signal recording for brain machine interface. This work presents a novel but simple method to fabricate high-density silicon (Si) microneedle arrays with various heights and diverse cross-sectional shapes depending on photomask pattern designs. The proposed fabrication method is composed of a single photolithography and two subsequent deep reactive ion etching (DRIE) steps. First, a photoresist layer was patterned on a Si substrate to define areas to be etched, which will eventually determine the final location and shape of each individual microneedle. Then, the 1st DRIE step created deep trenches with a highly anisotropic etching of the Si substrate. Subsequently, the photoresist was removed for more isotropic etching; the 2nd DRIE isolated and sharpened microneedles from the predefined trench structures. Depending on diverse photomask designs, the 2nd DRIE formed arrays of microneedles that have various height distributions, as well as diverse cross-sectional shapes across the substrate. With these simple steps, high-aspect ratio microneedles were created in the high density of up to 625 microneedles mm−2 on a Si wafer. Insertion tests showed a small force as low as 172 µN/microneedle is required for microneedle arrays to penetrate the dura mater of a mouse brain. To demonstrate a feasibility of drug delivery application, we also implemented silk microneedle arrays using molding processes. The fabrication method of the present study is expected to be broadly applicable to create microneedle structures for drug delivery, neuroprosthetic devices, and so on. Highlights: 1 High-density out-of-plane microneedle arrays were fabricated with a single photolithography and two deep reactive ion etching (DRIE) steps in anisotropic and isotropic modes, respectively. 2 Microneedles in various heights were monolithically created by the identical DRIE processes and scanning electron microscopy images showed extremely sharp sub-micron ( 145-nm-wide) tip. 3 Diverse cross-sectional shapes of microneedles were implemented by altering photomask patterns.